Clinical Characteristics, Mechanism, and Outcome of Humeral Shaft Fractures Sustained during Arm Wrestling in Young Men: A Retrospective Study - Junjie Shen; Pei Yu; Renhao Yang; Gen Li; Qi Sun; Ming Cai; Xianyou Zheng; Lei Wang (Orthopaedic Surgery, 2023)
Objective Humeral fractures are common in arm wrestling and other sports and military activities requiring similar movements; however, the precise mechanism is poorly understood. Here, we present an overview of the characteristics, possible mechanisms, and treatment of humeral shaft fractures sustained during arm wrestling. Methods We reviewed 8 years (January 2013 to January 2021) of medical records and retrospectively analyzed data from 27 patients with humeral shaft fractures sustained during arm wrestling. The clinical data included sex, age, affected arm, alcohol consumption, muscle warm‐up, history of competitive participation, opponents' characteristics, wrist position, and post‐fracture radial nerve injuries. The fracture configurations were radiographically assessed and analyzed. Surgical management included single or dual plating. Scores on the Disability of the Arm, Shoulder, and Hand questionnaire (DASH) were evaluated preoperatively and postoperatively at the last follow‐up visit. Results All fractures sustained during arm wrestling were spiral fractures of the distal third of the humerus. Of these, 11 were 12‐A1 type and 16 were 12‐B2 type with a wedge fragment. The two subtypes differed in the total fracture line length (12‐A1: 0.18 ± 0.04; 12‐B2: 0.23 ± 0.04; P < 0.001). The radial nerve injury rate was 0/11 (0%) in patients with 12‐A1 type fractures and 7/16 (43.8%) in patients with 12‐B2 type fractures (P = 0.011). Most patients were young men (mean age, ~25 years) with a history of competitively participating in arm wrestling for >2 years. Cold seasonal temperatures and a lack of warm‐ups increased the risk of injury. All patients showed improved DASH scores at the last follow‐up (12‐A1:77.82 ± 5.14 to 10.25 [5.38]; 12‐B2:78.91 ± 7.46 to 8.95 [3.17]; P < 0.001). No significant differences were observed among the different surgical treatments. Conclusions Individuals who participated in arm wrestling were at risk of humeral shaft fractures (type 12‐A1 or 12‐B2). The 12‐B2 type occurs with a wedge fragment and is frequently accompanied by radial nerve injuries. The characteristics of arm‐wrestling fractures and the mechanism(s) underlying these fractures can help orthopedic surgeons understand the causes of these fractures and similar fractures sustained in traditional sports. This understanding will help surgeons choose more effective surgical treatments that will result in more desirable functional outcomes and a faster return to work.